The Indonesian Government’s Dilemma in Repatriating Former ISIS Members: Balancing Advocacy, Citizenship Status, and Human Rights - Puteri, Dina Silvia; Wahono, Denita Cahyanti; Firdaus, Rr. Jannatul; Nte, Ngboawaji Daniel; Windiahsari, Windiahsari (Faculty of Law, Universitas Negeri Semarang, 2024)
Indonesian Government confronts a multifaceted challenge in repatriating former ISIS members, necessitating a delicate equilibrium between advocacy, citizenship status, and human rights principles. International conventions uphold the fundamental right to nationality, articulated in Article 15 of the Universal Declaration of Human Rights, yet over 500 former ISIS members from Indonesia remain stranded in Syria, having illegally departed and destroyed their official documentation. While several countries in Southeast Asia and Europe have undertaken repatriation efforts under rigorous conditions, Indonesia faces a quandary. These individuals do not qualify as People with Social Welfare Problems under domestic law, complicating their reintegration. This classification divergence conflicts with international obligations requiring nations to accept and restore nationality to their citizens, notwithstanding their affiliation with extremist groups not recognized as refugees by the UNHCR. This paper delves into the legal and humanitarian imperatives compelling Indonesia to address this issue. It examines international frameworks and national legislation to argue for the necessity of repatriation, while also exploring the preventive and repressive measures Indonesia employs. Balancing the imperative to safeguard human rights with national security concerns presents a formidable task, demanding a nuanced approach that ensures compliance with international standards while safeguarding domestic stability and security.